2019
DOI: 10.1007/s11409-019-09189-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of self-assessment feedback on self-assessment and task-selection accuracy

Abstract: Effective self-regulated learning in settings in which students can decide what tasks to work on, requires accurate self-assessment (i.e., a judgment of own level of performance) as well as accurate task selection (i.e., choosing a subsequent task that fits the current level of performance). Because self-assessment accuracy is often low, task-selection accuracy suffers as well and, consequently, self-regulated learning can lead to suboptimal learning outcomes. Recent studies have shown that a training with vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 52 publications
3
19
0
8
Order By: Relevance
“…Research abounds regarding the driving power of SA to self-efficacy (e.g., Brown & Harris, 2013;Kissling, E. & O' Donnell, 2015;McMillan & Hearn, 2008;Panadero et al, 2012Panadero et al, , 2013Panadero et al, , 2017Reybroeck et al, 2017), but studies on the reverse direction are scarce. Limited research reports divergent and inconclusive results as to whether and how self-efficacy informs SA (Chemers et al, 2001;Ivars et al, 2014;Shaban et al, 2016) despite the increasing recognition that accurate SA leads to accurate task selection, thus conducive to self-regulated learning and improved learning outcomes (Brown & Harris, 2013;McMillan & Hearn, 2008;Raaijmakers et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research abounds regarding the driving power of SA to self-efficacy (e.g., Brown & Harris, 2013;Kissling, E. & O' Donnell, 2015;McMillan & Hearn, 2008;Panadero et al, 2012Panadero et al, , 2013Panadero et al, , 2017Reybroeck et al, 2017), but studies on the reverse direction are scarce. Limited research reports divergent and inconclusive results as to whether and how self-efficacy informs SA (Chemers et al, 2001;Ivars et al, 2014;Shaban et al, 2016) despite the increasing recognition that accurate SA leads to accurate task selection, thus conducive to self-regulated learning and improved learning outcomes (Brown & Harris, 2013;McMillan & Hearn, 2008;Raaijmakers et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, prior work has demonstrated that providing students with instruction and training in making accurate self-assessment leads to better performance and greater monitoring accuracy [98,99], but providing students with only feedback on their accuracy can lead to greater overconfidence and less effective metacognitive control [100]. Given these findings, future work should investigate the effect that metacognitive training and feedback has on the ways in which students interact with solution videos.…”
Section: Discussionmentioning
confidence: 97%
“…Student self-assessment as a whole remains a topic of legitimate contention [2], and there are numerous issues warranting closer inspection [35]. However, under proper conditions, self-assessment results can generally be deemed reliable, with the ability of responders to participate critically in the assessment process tracking with age [39], experience [36], and ability [13]. Overestimation has long been determined to be more likely when the learner's grade is linked to the result of the self-assessment [7]; this factor is moot in the present study, as neither participation nor the responses in the survey had any effect on the course evaluation.…”
Section: Instrumentmentioning
confidence: 99%